2003
DOI: 10.1007/bf03030440
|View full text |Cite
|
Sign up to set email alerts
|

UV-B radiation affects chlorophyll and activation of rubisco by rubisco activase inCanavalia ensiformis L. leaves

Abstract: We studied the influence of UV-B radiation on chlorophyll and rubisco activation by rubisco activase in the leaves of jackbean (Canavalia ensiformis). Chlorophyll content was decreased, indicating that the synthesis of those molecules may have been degraded or repressed after exposure. Rubisco content was significantly lower in radiated tissue compared with the untreated control; rubisco activity showed a similar pattern of change. Based on these data, we suggest that rubisco activity is associated with the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
6
16
0
Order By: Relevance
“…In the two species, irradiation of B-UV significantly decreased not only total chlorophyll and carotenoids contents but also the chlorophyll ratio, resulting in more breakdown of chlorophyll 'a' in comparison with chlorophyll 'b'. Our results are similar to previous results (Choi and Roh, 2003;Zhang et al, 2005). Zhang et al (2005) found that direct UV-B lamps decreased chlorophyll contents and carotenoids as well as turf quality in Kentucky bluegrass.…”
Section: Chlorophylls and Carotenoidssupporting
confidence: 94%
“…In the two species, irradiation of B-UV significantly decreased not only total chlorophyll and carotenoids contents but also the chlorophyll ratio, resulting in more breakdown of chlorophyll 'a' in comparison with chlorophyll 'b'. Our results are similar to previous results (Choi and Roh, 2003;Zhang et al, 2005). Zhang et al (2005) found that direct UV-B lamps decreased chlorophyll contents and carotenoids as well as turf quality in Kentucky bluegrass.…”
Section: Chlorophylls and Carotenoidssupporting
confidence: 94%
“…V cmax is affected by factors that determine the level of activated enzyme (Rubisco), which is determined by the foliar chlorophyll concentrations. These factors include temperature (Sage, 2002), water stress (Flexas et al, 2006), leaf nitrogen content (Maroco et al, 2002;Gonzalez-Real and Baille, 2000), radiation intensity (Choi and Roh, 2003), salt stress (Centritto et al, 2003) and a combination of the aforementioned factors. Under environmental stress, chlorophyll levels decrease and induce a decrease in V cmax (Houborg et al, 2013), because leaf chlorophyll levels are the primary factor that control spectral reflectance variation in the visible light regions and dominantly control the solar radiation levels that a leaf absorbs.…”
Section: Introductionmentioning
confidence: 99%
“…The research by Keiler et al [8] and Choi and Roh [9] proved that UV-B radiation destroyed photosynthesis by decreasing the carbon dioxide deoxidize reaction, content, and activation of Rubisco. Strid [10] and Jansen [11] also indicated that UV-B radiation reduced the pigment content, closed the mad stoma, and changed the plant shape.…”
mentioning
confidence: 99%